Análise das tensões em elementos de contraventamento de edifícios em alvenaria estrutural - Lima, José Ricardo Donin de (2008)
The challenge of conceiving buildings each time higher and higher in structural masonry makes away to look for to the improvement of the calculation processes, in a way to optimize the structures. A factor of great importance in the project of the masonry is the consideration of the board of compression effect in the resistance of the walls of the construction, mainly for those where the action of the wind is more significant. Another aspect of great relevance is the analysis of structural safety's concepts in the calculation of the masonry. In this work the analysis of the active tensions is accomplished in the elements of resistance of a building of ceramic structural unreinforced masonry, with eight pavements, according to the considerations of the Brazilian Norms NBR 10837:1989 and NBR 8681:2003, of the British Standard BS 5625:1992, and by the numeric modelling through the Finite Element Method. Starting from the obtained results, it can be verified that are significant the variations in the results of tensions, obtained starting from the normative considerations; and that the numeric methods, that consider a very larger universe of factors, they allow a much more discerning analysis of the state of tensions that the structure is submitted. The analysis of structural safety's concepts in the calculation of the masonry is of fundamental importance for the project of the structure.